Informasi Yang Menyesatkan Dalam Prospektus: Bagaimanakah Tanggung Jawab Hukum Emiten? - Celina Tri Siwi K.; Meredith Fiona Effendi; Hermanto Silalahi (Universitas Katolik Widya Karya Malang, 2024)
Prior to conducting a public offering, issuers are required to submit a company report called a prospectus that contains information about financial or non-financial statements. However, it become a gap for issuers by providing a prospectus contains misleading information where information provided is incomplete or issuer exaggerates a report of material fact. The formulation of the problem in this study is whether the issuer's legal liability due to misleading information in the prospectus on public offering transactions in the capital market has provided justice to investors and how to resolve if the issuer harms investors if there is misleading information in the prospectus on public offering transactions in the capital market. The research method used by the author in this study is a type of juridical normative and empirical juridical research. The results show that the issuer has to provide compensation to investors resulting from negligence in making a misleading prospectus. Efforts to resolve disputes if investors are harmed by way of complaints to the OJK.The advice that can be given is that if the issuer wants to make a public offering, before that, he must make the actual information, namely the information provided is not reduced or exaggerated.